PERAN SATGAS PERLINDUNGAN PEREMPUAN DAN ANAK DALAM PERLINDUNGAN ANAK KORBAN KEKERASAN SEKSUAL DI DESA JATIREJO KECAMATAN GIRIMARTO KABUPATEN WONOGIRI - Utari Murni Adhi; Susi Sulandari (Journal of Public Policy and Management Review, 2019)
Child sexual violence happens increasingly nowadays. Some efforts are needed from the government to protect the children of sexual violence victims. Through the Wonogiri Regent Decree No. 198 of 2017, a Task Force for the Protection of Women and Children was established at the village level in an effort to protect the children victims of sexual violence. One of the villages that forms the Women and Children Protection Task Force is Jatirejo Village. Women and Children Protection Task Force of Jatirejo Village has duties and functions of receiving complaints, conducting outreach, identifying, providing temporary protection, evacuating, making recommendations, and socializing. The objectives of this research were to describe and analyze the role of Women and Children Protection Task Force in the children protection of victim of sexual violence in Jatirejo Village and to describe the obstacles related to the practice of roles by Women and Children Protection Task Force in Jatirejo Village. This research used descriptive qualitative research design. Data collection techniques used were observation, interviews, and documentation. Data analysis was done by collecting data, reducing data, presenting data, and drawing conclusions. The results showed that Women and Children Protection Task Force in Jatirejo Village had carried out its role in protecting children victims of sexual violence, however, the practice of these roles was still not optimal in which there were still flaws in several sectors. Moreover, there were also some obstacles in human resources and absence of the budget. The suggestions given were increasing the intensity of meetings for members, dividing the working hours, dividing the tasks, increasing the intensity of socialization, cooperation with stakeholders for training about child protection and allocating the budget.